Revitalizing degraded and abandoned lands: reflections from local government involvement in mud brick production - Tanzania - Genda, Elizabeth Lulu; Mamkwe, Claudia Edward (African Journal of Empirical Research, 2024)
A paper submitted African Journal of Empirical Research VOL. 5 NO. 1 (2024):JAN-MAR 2024